1944
DOI: 10.1152/ajplegacy.1944.141.4.575
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Chloride Concentration in Human Sweat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1948
1948
1975
1975

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…It might therefore be expected that, as the subjects had lower rectal temperatures when taking salt than when not taking salt, the chloride content of their sweat would also be lower. This has been reported by Johnson et al (1944) and by Lee et al (1941). But a low daily salt intake diminishes the salt loss in the sweat (McCance, 1938) and a high salt intake increases the chloride content of arm sweat (Ladell, 1945) also of whole body sweat (Weiner & van Heyningen, 1952b).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It might therefore be expected that, as the subjects had lower rectal temperatures when taking salt than when not taking salt, the chloride content of their sweat would also be lower. This has been reported by Johnson et al (1944) and by Lee et al (1941). But a low daily salt intake diminishes the salt loss in the sweat (McCance, 1938) and a high salt intake increases the chloride content of arm sweat (Ladell, 1945) also of whole body sweat (Weiner & van Heyningen, 1952b).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, Adolph (1947 a) is quite definite that sweat rate is independent of water intake, and the Fort Knox team (Eichna, Bean, Ashe & Nelson, 1945) found that replacing the sweat losses did not affect the sweat rate. In some tests saline has been given in place of water; Lee, Murray Simmonds & Atherton (1941) found a reduction in sweat rate with saline, more marked in hot dry conditions; Johnson et al (1944) reported the same, although the same team ) also reported the opposite in another paper. Eichna et al found no effect at all, and Gerking & Robinson (1946) in contrast to Johnson did not find that drinking of saline deferred the onset of sweat gland 'fatigue'.…”
mentioning
confidence: 96%
“…Although sweat solute concentrations vary greatly in different body areas, there is no evidence that the arm sweat concentrations of the measured solutes are higher than the concentration of these solutes from other skin areas collected in a similar manner (4,5,6,14,26). It would appear that the environment created under the arm bag led to the differences noted between arm and total body sweat solute concentration.…”
Section: Discussionmentioning
confidence: 87%
“…The mean chloride concentration in 187 samples of sweat from subject H was 0 275 %, standard deviation 0-082; the mean concentration in 281 samples from subject B was 0 469 %, standard deviation 0X091. The factors concerned in these variations are many (Johnson et al 1944 …”
Section: Total Loss For Whole Exposurementioning
confidence: 99%